Effect of mild strain on severity of PRSV-W infection - Rahman, MF; Akanda, MA; Sarkar, MZA (Bangladesh Journal of Agricultural Research, 2010)
Studies were conducted to develop mild/avirulent strain of PRSV-W using nitrous acid, sodium azide and UV-radiation for the mutagenic treatments. Among the three mutagens’ sodium azide at 3%, 4%, and 5%, and nitrous acid at 0.1M and 0.125M were proved to be effective in producing mild/avirulent strains of PRSV-W, while UV-radiation was proved to be ineffective. Evaluation on the effectivity of mild/avirulent strains in net house in protecting severe strain of PRSV-W proved that the efficiency of mild/avirulent strain to protect the severe strain of the virus was dependent upon the time gap between the mild strain inoculation and challenge inoculation. The challenge inoculation with the severe strain of PRSV-W after 12 days of mild strain inoculation could confer the cross-protection in about 64% pumpkin plants upto 40 days. The presence of mild/avirulent strains of PRSV-W in the asymptomatic plants challenged with severe strain of PRSV-W was tested by mechanical inoculation of Chenopodium amaranticolor to observe the development of characteristic local lesions of PRSV-W. Keywords: PRSV; cross protection. DOI: 10.3329/bjar.v35i2.5891 Bangladesh J. Agril. Res. 35(2) : 279-285, June 2010